Anais Do XXIX Workshop Sobre Educação Em Computação (WEI 2021) 2021
DOI: 10.5753/wei.2021.15908
|View full text |Cite
|
Sign up to set email alerts
|

Uma Análise Preliminar da Aplicação do Método 300 em Turmas de Algoritmos e Programação

Abstract: As dificuldades de aprendizado de algoritmos e programação representam uma das razões para os altos índices de evasão nos primeiros anos dos cursos da área de computação e informática. Tal fato vem motivando a busca e a aplicação de novas estratégias de ensino. Neste cenário, as metodologias ativas de aprendizagem apresentam-se como uma alternativa, auxiliando o professor em atividades que promovam maior interação entre os alunos, aumentando o engajamento e as possibilidades de aprendizagem. Este trabalho apre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…M300 method can be defined as an innovative strategy of active learning, combining features of peer learning and mentoring techniques, which are widely used in active learning (de Castro Junior et al, 2021). POGIL is a suitable pedagogical approach for teaching programming, software testing, and DevOps at the undergraduate level (Joshi and Lau, 2023).…”
Section: Sq1 Which Alms Were Addressed In the Publications?mentioning
confidence: 99%
See 1 more Smart Citation
“…M300 method can be defined as an innovative strategy of active learning, combining features of peer learning and mentoring techniques, which are widely used in active learning (de Castro Junior et al, 2021). POGIL is a suitable pedagogical approach for teaching programming, software testing, and DevOps at the undergraduate level (Joshi and Lau, 2023).…”
Section: Sq1 Which Alms Were Addressed In the Publications?mentioning
confidence: 99%
“…In this sense, it is observed that the DOJO (S61, S63), TBL (S20), JE (S11), and PBL (S9) were the methodologies that most contributed to the awakening of Collaboration among students and between students and instructors. In the case of the DOJO, in addition to making the experience more fun, it promotes an inclusive, cooperative, and collaborative environment based on exchanging experiences and networking among participants (de Castro Junior et al, 2021). This occurs because this ALM allows for improved classroom participation and knowledge exchange via collaboration in activities and discussions.…”
Section: Sq5 What Evaluation Metrics Were Reported In the Publications?mentioning
confidence: 99%